Distinct regulation of tonsillar immune response in virus infection. Issue 5 (29th March 2014) - Jartti, T.; Palomares, O.; Waris, M.; Tastan, O.; Nieminen, R.; Puhakka, T.; Rückert, B.; Aab, A.; Vuorinen, T.; Allander, T.; Vahlberg, T.; Ruuskanen, O.; et al.
Abstract Background The relationships between tonsillar immune responses, and viral infection and allergy are incompletely known. Objective To study intratonsillar/nasopharyngeal virus detections and in vivo expressions of T‐cell‐ and innate immune response‐specific cytokines, transcription factors, and type I/II/III interferons in human tonsils. Methods Palatine tonsil samples were obtained from 143 elective tonsillectomy patients. Adenovirus, bocavirus‐1, coronavirus, enteroviruses, influenza virus, metapneumovirus, parainfluenza virus, rhinovirus, and respiratory syncytial virus were detected using PCR. The mRNA expression levels of IFN‐α, IFN‐β, IFN‐γ, IL‐10, IL‐13, IL‐17, IL‐28, IL‐29, IL‐37, TGF‐β, FOXP3, GATA3, RORC2, and Tbet were directly analyzed by quantitative RT‐PCR. Results Fifty percentage of subjects reported allergy, 59% had ≥1 nasopharyngeal viruses, and 24% had ≥1 intratonsillar viruses. Tonsillar virus detection showed a strong negative association with age; especially rhinovirus or parainfluenza virus detection showed positive association with IFN‐γ and Tbet expressions. IL‐37 expression was positively associated with atopic dermatitis, whereas IFN‐α, IL‐13, IL‐28, and Tbet expressions were negatively associated with allergic diseases. Network analyses demonstrated strongly polarized clusters of immune regulatory (IL‐10, IL‐17, TGF‐β, FOXP3, GATA3, RORC2, Tbet) and antiviral (IFN‐α, IFN‐β, IL‐28, IL‐29) genes. These two clusters became more distinctive in the presence of viral infection or allergy. A negative correlation between antiviral cytokines and IL‐10, IL‐17, IL‐37, FOXP3, and RORC2 was observed only in the presence of viruses, and interestingly, IL‐13 strongly correlated with antiviral cytokines. Conclusions Tonsillar cytokine expression is closely related to existing viral infections, age, and allergic illnesses and shows distinct clusters between antiviral and immune regulatory genes.